A quantitative and qualitative examination of the impacts of the COVID-19 pandemic on U.S. veterans with self-reported anxiety and alcohol use disorder - Duarte, Brooke A.; Kelly, Megan M.; Shirk, Steven D.; Chamberlin, Elizabeth S.; Reilly, Erin D. (Frontiers in Psychiatry, 2023)
Introduction The COVID-19 pandemic generated concerns about rising stress and alcohol use, especially in U.S. veterans who experience high rates of anxiety disorders (ADs), alcohol use disorder (AUD), and dual AD+AUD diagnoses. This study investigated differences among these diagnostic groups in a veteran population related to their concern about COVID-19, impacts of COVID-19 on quality of life, and self-reported changes to urge to drink and drinking frequency. Methods A nationally administered online survey was given to a sample of U.S. veterans reporting substance use issues during the pandemic. Differences in the level of concern about COVID-19, impacts of COVID-19 on quality of life, and drinking behaviors were examined in those self-reporting AD (n = 98), AUD (n = 46), or AD+AUD (n = 67). Consensual qualitative research was used to analyze an open-ended question about COVID-19’s impact on substance use, health, and quality of life. Results Veterans with AD+AUD experienced significant increases in urge to drink and alcohol consumption compared to veterans with AD only. Greater urge and frequency of drinking were associated with greater negative impacts of COVID-19 on quality of life. There were no differences among groups in global negative impact on quality of life or level of COVID-19 concern. However, respondents described specific COVID-19 worries, with qualitative findings revealing that those with AD+AUD reported a disproportionate psychosocial burden due to the pandemic. Discussion Special attention in screening and treatment should be given to those with a dual AD+AUD diagnosis who may be experiencing both an increase in alcohol use and psychosocial burden as stress increases due to the pandemic.